Oral health knowledge and practices among primary healthcare workers in Shimla District, Himachal Pradesh, India - Bhardwaj, V. (Wolters Kluwer Medknow Publications, 2018)
Context: Primary healthcare workers being grassroot workers in rural areas can be effective in oral health promotion in these areas. Aim: To assess oral health knowledge and practices among primary healthcare workers in Shimla district in Himachal Pradesh. Setting and Design: A cross-sectional study. Subjects and Methods: A cross-sectional study was conducted to assess oral health knowledge and practices of primary healthcare workers in Shimla using a self-administered questionnaire. Statistical Analysis Used: Data were analyzed using SPSS package version 16. The tests used were t-test and Fisher's exact test. A P value < 0.05 was considered statistically significant. Results: Of 130 subjects, there were 60 (46.2%) males and 70 (53.8%) females. The mean age of the population was 48.4 ± 5.9 with a range of 25-57. The mean knowledge score percent of the population was 51.9 ± 18.2. It was higher for males (52.3 ± 15.0) when compared with females (51.5 ± 20.7). The mean knowledge score percent was positively associated with education and negatively associated with age. Tooth brush was used by 97.7% and tooth paste by 121 (93.1%). The frequency of brushing twice was reported by 79 (60.8%). Conclusion: Though the overall knowledge about oral health is good among primary healthcare workers, the understanding about various aspects is lacking. Therefore, it is recommended that health workers should be given education to enhance knowledge and practices toward oral healthcare and to increase their screening capacity for common dental problem which will serve the community in long way. © 2018 Indian Journal of Dental Research | Published by Wolters Kluwer - Medknow.